Freshwater Fish and Challenge of Supply Chain for Production Enhancement: West Southern Region of Aceh Province, Indonesia - Zuriat, Zuriat; Amarullah, T; gazali, mohamad; Ali, M; Irham, Muhammad (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2025)
This research aims to analyze the supply chain and marketing chain of freshwater fish in the West-Southern Region of Aceh Province, Indonesia. The research activities took place from May to July 2022, with data collection continuing in 2023. The determination of data collection locations used purposive methods, and data collection was conducted through survey methods. Data were obtained from fish traders in four  markets: Ujong Baroh Meulaboh Fish Market, Blang Pidie Market, Nagan Raya Market, and Krueng Sabe Fish Market. Data analysis was conducted descriptively. The research results indicate that the supply chain includes fish farmers, partner traders, collector traders, retailers, and consumers, and there are two supply chains based on regions: inter-insular and intra-region. The dominant types of freshwater fish supply are catfish and tilapia. Tilapia has a higher price compared to catfish. Tilapia is dominant in the Ujong Baroh market, while catfish is dominant in the Blang Pidie  market. It has become a substitute when sea fish are scarce or expensive in the market. Based on the value chain analysis, a margin ranging from 10% to 30% was obtained. Partner traders play a significant role in production activities and the supply chain due to cooperation in input-output factors. Challenges in the freshwater fish supply consist of seeds and feed, with seeds mostly supplied from outside West-South, accounting for more than 80%.. Addressing freshwater fish supply challenges in Southwest Aceh requires an integrated supply chain approach enhancing hatchery systems and fry distribution upstream, improving aquaculture infrastructure and feed subsidies at the production level, and establishing collection centers, cold storage, and modern markets in key districts to strengthen distribution, stabilize prices, and improve food security.